The Influence of Video Educational Media on Adolescents' Knowledge About the Dangers of Abusing Aibon Adhesive Among 8th Grade Students at SMP Negeri 3 Sorong City - Fitriani, Fitriani; Emray, Joan; Tyas, Lusia Wahyunig; Andirwana, Andirwana (Jurnal Kesehatan Pasak Bumi Kalimantan, 2025)
Background: According to the World Health Organization (2022), adolescence is a period that lies between childhood and adulthood in the age range of 10 to 19 years. Based on a survey conducted by the National Narcotics Agency (BNN), there was an increase in the number of addictive substance abuse in Indonesia among high school students from 18,000 to 73,523. In 2017, the number of cases of glue use in West Papua Province had reached around 900 cases (Rosalina, 2019). Data obtained from respondents of class VIII students at SMP Negeri 3 Sorong City, namely, higher respondents who have never smoked glue (97.3%), compared to respondents who have smoked glue (2.7%). . Objective: This study aims to determine whether there is an effect of video education media on adolescents' knowledge about the dangers of glue addictive substance abuse at SMP N 3 Sorong City. Methods: This type of research is a quantitative study using pre-experimental with a one group pre and post test design. The population of this study were all VIII grade students of SMP Negeri 3 Kota Sorong which amounted to 347 people and the research sample amounted to 185 respondents. The sampling technique in this study used stratified random technique. The research instrument used was a questionnaire. The statistical test used is the Wilcoxon sign rank test. Results: The results showed that there was an effect of video education media on adolescents' knowledge about the dangers of glue addictive substance abuse in class VIII students at SMP Negeri 3 Sorong City with a p-value = 0.000 (<0.05). The conclusion is that there is an effect of video education media on adolescents' knowledge about the dangers of glue addictive substance abuse. Conclusion: The conclusion of this study is that there is an effect of video education media on adolescents' knowledge about the dangers of glue addictive substance abuse in class VIII students at SMP Negeri 3 Kota Sorong. Suggestions for students of SMP Negeri 3 Kota Sorong are expected from the results of this study students have broad knowledge and insight into the dangers of addictive substance abuse of glue to not fall into the wrong association. Keywords: Adolescents, Video Media, Substance Abuse